The mental burden of stay-at-home order extensions during COVID-19 - Michelle S. Segovia; Samir Huseynov; Marco A. Palma; Rodolfo M. Nayga (Scientific Reports, 2024)
Abstract This study evaluates the psychological impact of stay-at-home extension orders during COVID-19 and its relationship with individuals’ expectations on the duration of the extensions. An online survey was administered to 1259 US adult residents to measure symptoms of post-traumatic stress disorder (PTSD), anxiety and stress induced by different stay-at-home order extensions using hypothetical length scenarios. We find that individuals exposed to two 2-week order extensions exhibit higher levels of stress and anxiety compared to those exposed to a single 4-week extension. We also find that subjects with longer expected extensions exhibit more signs of psychological damage than those with shorter expected extensions. Furthermore, we find that the negative psychological consequences of providing two shorter extensions is observed only among subjects with extension expectations of four weeks or less. Our results demonstrate that people’s expectations affect the level of psychological damage caused by lockdown mandates. Our findings suggest that whenever lockdown extensions are necessary, reduced psychological distress may be possible by implementing a one-time restriction, rather than extending multiple smaller extensions perhaps due to manipulation of personal expectations.